Halogen-free ionic liquids as excellent lubricants for PEEK-stainless steel contacts at elevated temperatures. (December 2016) - Wu, Jian; Lu, Xiaohua; Feng, Xin; Shi, Yijun
Abstract: Advanced polymers sliding against steel under ionic liquids (ILs) has great potential applications. However, halogen-containing ILs (h-ILs) often induce high corrosive wear to steel. In this work, halogen-free ILs (hf-ILs) were used as neat lubricants to investigate the performance of poly(ether-ether-ketone)-AISI304 stainless steel (PEEK-304ss) contacts at elevated temperatures. The results indicate that hf-ILs with short alkyl chains show excellent anti-corrosion and antiwear properties. The wear rates of 304ss lubricated by hf-ILs at 160 °C are 3–71% of those by h-ILs. The friction coefficients of PEEK-304ss lubricated by hf-ILs are just 13–33% of those by h-ILs. The excellent performance of hf-ILs can be attributed to the reason that hf-ILs will not generate any halogen containing acid during the test. Graphical abstract: Highlights: Halogen-free ILs (hf-ILs) lubricate PEEK-stainless steel at elevated temperature. Hf-ILs with short alkyl chains show excellent anti-corrosion and antiwear properties. Friction coefficient under hf-ILs at 160 °C is 13–33% of that under halogen-containing ILs. Hf-ILs can work as excellent lubricants for PEEK-stainless steel with little/no corrosion problems.